Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain (1332675) (2024)
The escalating issue of air pollution has become a significant concern in urban regions, including Islamabad, Pakistan, due to the rise in air pollutant emissions driven by economic and industrial expansion. To gain a deeper understanding of air pollution, a study was conducted during winter 2022–2023, assessing physical, chemical, and biological factors in Islamabad. The findings revealed that the average concentration of fine particulate matter (PM2.5) was notably greater than the World Health Organization (WHO) guidelines, reaching 133.39 μg/m³. Additionally, the average concentration of bacteria (308.64 CFU/m³) was notably greater than that of fungi (203.55 CFU/m³) throughout the study. Analytical analyses, including SEM-EDS and FTIR, showed that the PM2.5 in Islamabad is composed of various particles such as soot aggregates, coal fly ash, minerals, bio-particles, and some unidentified particles. EF analysis distinguished PM2.5 sources, enhancing understanding of pollutants origin, whereas Spearman's correlation analysis elucidated constituent interactions, further explaining air quality impact. The results from the Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-OES) indicated a gradual increase in the total elemental composition of PM2.5 from autumn to winter, maintaining high levels throughout the winter season. Furthermore, a significant variation was found in the mass concentration of PM2.5 when comparing samples collected in the morning and evening. The study also identified the presence of semi-volatile organic compounds (SVOCs) in PM2.5 samples, including polycyclic aromatic hydrocarbons (PAHs) and phenolic compounds, with notable variations in their concentrations. Utilizing health risk assessment models developed by the US EPA, we estimated the potential health risks associated with PM2.5 exposure, highlighting the urgency of addressing air quality issues. These findings provide valuable insights into the sources and composition of PM2.5 in Islamabad, contributing to a comprehensive understanding of air quality and its potential environmental and health implications. Other Information Published in: Environmental Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envres.2024.118862